The Influence of Information Services Using Video Media on the Career Selection of Junior High School Students - Fatimah, Rina; Yuliejantiningsih, Yovitha; Ismah, Ismah (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This study aims to explore the effectiveness of video media in providing information that can influence learners' career decisions, which in turn can improve their understanding of the world of work and guide them toward more appropriate and realistic career choices. The study was conducted at SMP Negeri 34 Semarang in 2023. This research used a quasi-experimental design with a nonequivalent control group design model. The data collection technique used was a questionnaire of students' career choices, and data analysis was done using descriptive statistics. The analysis showed that the F-count value was 5.333 with a significance level of 0.036 <0.05, so information services with video media affected the career selection of third-grade students at SMP Negeri 34 Semarang. The study's conclusion reveals that information services with video media affect the career selection of third-grade students at SMP Negeri 34 Semarang. The research contributes to the field of guidance and counseling, especially regarding the use of video media as an effective information tool in helping students understand career choices.